Gender, Conflict, and Development - Tsjeard Bouta, Georg Frerks (The World Bank)
Gender, Conflict, and Development was written as an effort to fill a gap between the Bank’s work on gender mainstreaming and its agenda in conflict and development. The authors identify a link between gender and conflict issues and provide the most comprehensive review of external and internal sources on gender and conflict, with a particular focus on policy relevance for an institution such as the Bank.